2021
DOI: 10.1038/s41522-021-00259-8
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial vaginosis and health-associated bacteria modulate the immunometabolic landscape in 3D model of human cervix

Abstract: Bacterial vaginosis (BV) is an enigmatic polymicrobial condition characterized by a depletion of health-associated Lactobacillus and an overgrowth of anaerobes. Importantly, BV is linked to adverse gynecologic and obstetric outcomes: an increased risk of sexually transmitted infections, preterm birth, and cancer. We hypothesized that members of the cervicovaginal microbiota distinctly contribute to immunometabolic changes in the human cervix, leading to these sequelae. Our 3D epithelial cell model that recapit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 140 publications
(153 reference statements)
13
61
0
Order By: Relevance
“…Lactobacilli play an important role in the defense to pathogens through their ability to produce lactic acid and maintain a low pH, which is harmful to most pathogens [ 132 ]. In contrast, vaginal dysbiosis is associated with an increase in pH, the induction of local inflammation and release of chemotactic mediators [ 133 ]. Indeed, the increased microbial diversity typical of vaginal dysbiotic states, is associated with the production of pro-inflammatory cytokines and chemokines, as was shown in women with low abundance of lactobacilli, possibly through the activation of the NF-κB signaling pathway [ 134 ].…”
Section: Importance Of Clinical Parameters and Hpv Genotype In The Na...mentioning
confidence: 99%
“…Lactobacilli play an important role in the defense to pathogens through their ability to produce lactic acid and maintain a low pH, which is harmful to most pathogens [ 132 ]. In contrast, vaginal dysbiosis is associated with an increase in pH, the induction of local inflammation and release of chemotactic mediators [ 133 ]. Indeed, the increased microbial diversity typical of vaginal dysbiotic states, is associated with the production of pro-inflammatory cytokines and chemokines, as was shown in women with low abundance of lactobacilli, possibly through the activation of the NF-κB signaling pathway [ 134 ].…”
Section: Importance Of Clinical Parameters and Hpv Genotype In The Na...mentioning
confidence: 99%
“…For example, recent examination of urinary isolates of L. crispatus found that they use phenyl-lactic acid to inhibit growth of uropathogens E. coli and E. faecalis ( Abdul-Rahim et al., 2021 ). This shows similarity of the L. crispatus urinary strains with relatives from the vagina as well as diverse food sources ( Jacobsen et al., 1999 ; Valerio et al., 2004 ; Hütt et al., 2016 ; Łaniewski and Herbst-Kralovetz, 2021 ). Additionally, mixed urinary bacterial communities from asymptomatic postmenopausal women and those with acute UTI were shown to interact differently, supporting the idea of complex intermicrobial interactions within the urinary microbiome and potential differential effects on UTI progression ( Zandbergen et al., 2021 ).…”
Section: Introductionmentioning
confidence: 62%
“…with the highest fold change (1150-fold) of all the metabolites measured. Although the role of this metabolite in the cervicovaginal microenvironment is still not clear, we have previously observed its accumulation following infections with other vaginal bacteria ( Łaniewski and Herbst-Kralovetz, 2021 ; Salliss et al., 2021 ). The severity of BV has been associated with increased risk of HIV and other STI acquisition ( Allsworth and Peipert, 2011 ); thus, contribution of Eggerthella spp.…”
Section: Discussionmentioning
confidence: 98%
“…Organotypic 3-D human cervical epithelial cell models recapitulate many features of parental tissue that are not observed in monolayer cell culture models. Our advanced 3-D cell culture model exhibits physiologically relevant features, such as TLR expression, microvilli, intercellular junctional complexes and secretory material that could influence how BV-associated bacteria can colonize the model in a way similar to in vivo tissues ( Gardner et al., 2020 ; Łaniewski and Herbst-Kralovetz, 2021 ; Salliss et al., 2021 ) These features provide a more accurate representation of the in vivo state which is more amenable to translational research efforts and studying host-microbe interactions; however, each model system has its strengths, weaknesses and utility ( Hjelm et al., 2010 ; Radtke and Herbst-Kralovetz, 2012 ; Radtke et al., 2012 ; Herbst-Kralovetz et al., 2016 ). The close relation of 3-D human cervical epithelial cells to cervical tissue allows us to investigate how these pathogens can cause pathophysiological changes to the cervicovaginal microenvironment and epithelia.…”
Section: Discussionmentioning
confidence: 99%